Typological analysis of cultural heritage applications in city brand identity design - Liu, Qing; Shmelova-Nesterenko, O. (Art and Design, 2025)
This study investigated the diverse ways in which cultural heritage was integrated into city brand identity design. The purpose of the study was to identify and categorise distinct typologies of cultural heritage application across key visual elements – specifically logos and slogans, colour palettes, and auxiliary graphics. Employing a qualitative research approach, a typological analysis was conducted on diverse international case studies representing various cultural contexts and branding strategies. The analysis extended beyond visual aesthetics to examine the underlying semiotic principles, cognitive mechanisms, and cultural values that contribute to the effectiveness of these branding elements. The study revealed different typologies of integration of cultural heritage into the city’s brand identity. Each element demonstrated significant potential for utilising cultural heritage to enhance brand resonance and impact. Among the analysed cases, prominent examples included the iconic “I love NY” logo as a symbol of civic unity; Kawasaki’s, Busan’s, and Madrid’s updated slogans and logos reflecting new urban visions; the culturally grounded colour schemes of Nevers and Cairo; and the auxiliary graphics of Bologna and Baku, rooted in architectural and artisanal traditions. At the theoretical level, the study covered the evolution of the city logo along with the growth of social development, the way of integrating the city brand standard colour with cultural products and architecture, and the expression of cultural imagery in the auxiliary graphic design of simplicity, extraction, and reorganisation. In practical terms, the findings provided valuable insights for urban planners, designers, and branding professionals. The developed typological framework served as a practical tool for analysing existing branding strategies and formulating new, culturally sensitive approaches that effectively leverage heritage, thereby improving the overall impact of city branding initiatives.